Educational public management and the work environment in academic institutions - Mendieta Delgado, David E. (2022)
The type of research as a fundamental tool for the advancement of the study that allowed testing the hypothesis was the correlational type. Its purpose is to measure the degree of relationship that exists between two variables, in a particular context. The method was the analytical one that allowed us to make a clear interpretation of the theories included in the theoretical framework. Once the academic interest of the research and the corresponding guideline have been established, we are in a position to express the following result: The work carried out, both at the project level and in the thesis report, yielded the following result: As the p – value = 0.008 is less than the significance level = 0.06, then the null hypothesis is rejected, consequently it is affirmed that there is a significant relationship between educational public management and the work environment; Likewise, according to the rho value = 0.402, it is evident that educational public management and the work environment have a moderate positive relationship with a trend very close to a low positive relationship, indicating that educational public management has to improve to strengthen the work environment. Determined that there is a moderate  correlation of r= 0.589 between educational public management and the pedagogical management dimension of teachers,  indicating a moderate positive correlation, and it is an indicator that the indicated dimension has to be improved to strengthen and improve the work environment. It was determined that there is a significant correlation of r = 0.58 between variable X with the administrative management dimension and the work environment, and they show a moderate positive correlation indicating that educational public management has to improve to strengthen the work environment. It was determined that there is a significant correlation of r = 0.499 between educational public management and the institutional management dimension, and they show a moderate positive correlation indicating that the indicated dimension has to improve to strengthen the work environment.